Способ определения осмия инверсионно-вольтамперометрическим методом в природном и техногенном сырье - Горчаков Э. В. Эдуард Владимирович; Устинова Э. М. Эльвира Маратовна; Глызина Т. С. Татьяна Святославовна; Колпакова Н. А. Нина Александровна; Михайлов М. В. Максим Валентинович
опубл. 27.06.13